HAK ASASI DAN KEWAJIBAN BELA NEGARA DALAM KEBIJAKAN VAKSINASI COVID-19 DI INDONESIA - Wicaksono, Yudi Krisno; Nurjaya, I Nyoman; Susilo, Edi (Jurnal Agregasi, 2022)
This research study aims to examine the COVID-19 vaccination policy which is realized nationally in the perspective of the rights and obligations of citizens. This research method uses a normative legal approach, which combines a statute approach and a conceptual approach. The research findings show that health, including the human rights sector, is guaranteed by the constitution and legislation. The health crisis due to the impact of COVID-19 makes the fulfillment of citizens' human rights in the health sector very urgent to implement. Efforts are made to vaccinate in order to stop the spread of the virus and restore all state activities. The realization of the national vaccination program includes the fulfillment of rights and obligations in health facilities guaranteed in Law No. 6/2018 concerning Health Quarantine and Law No. 4 of 1984 regarding the Outbreak of Infectious Diseases. Citizens' rights to health insurance are stipulated in articles 28 and 34 of the 1945 Constitution. The perspective of the obligation in the vaccination program can be seen from Article 28 J paragraph 1 and also 2, the participation of citizens in vaccination is also included in efforts to provide a defense in accordance with Article 27 of the Constitution. 1945. The public may be subject to sanctions if they intentionally or unintentionally obstruct efforts to overcome the epidemic. Vaccination is expected to increase one's own immunity which will encourage the recovery of health, economy and national activities.